Causes of tooth loss in adults of different age - A. K. Iordanishvili; A. G. Slugina; N. V. Lapina; A. A. Serikov (Кубанский научный медицинский вестник)
The paper presents the results of a clinical study of primary medical documents dental clinic 8470 people (3613 men and 4857 women) aged 22 to 93 years in order to study the causes of the removal of natural teeth. Patients who had teeth removed 10 597, for various reasons, were divided by age and sex. Established age particularly the loss of teeth, which are not dependent on gender. During one visit to the dentist-surgeon people elderly are removed, respectively, 1.31 and 1.95 of the tooth. Information relevant to the organizers of dental care, dentists and specialists in gerontology and geriatrics.